Rethinking the God of the Gaps Argument: An Islamic Philosophical Critique of New Atheism - Muslih, Mohammad Kholid; Miqdad Hamid al Anshory; Aldy Pradhana (The Faculty of Ushuluddin and Humanities, Universitas Islam Negeri Walisongo Semarang, Indonesia, 2025)
The persistent claim by New Atheists that belief in God merely functions as a placeholder for ignorance—commonly referred to as the